Rancang Bangun Sistem Informasi Persewaaan Alat Berat Berbasis Web dengan GPS Tracker - Hargokendar Suhud; Fitro (LPPM Politeknik Pratama Kendal, 2022)
Rental of heavy equipment is the main business of PT. Tatabumi Adhiraya. In the rental business, PT. Tatabumi Adhiraya not want any loss that may be experienced by PT. Tatabumi Adhiraya as the owner of the heavy equipment and customers as service users heavy equipment. Reporting system with manually recording still certainly will affect the company's performance. It is considered less effective and efficient in supporting employee productivity and satisfaction will certainly affect the customer plus their high mobility leaders of PT. Tatabumi Adhiraya and those customers who do not always be in one place for long periods of time. Of these problems led to the idea to create a web-based application with GPS Tracker, which can perform recording therein the use of heavy equipment in real time and the results can be seen directly by the company and its customers. Pengembaangan method used system is SDLC (System Development Life Cycle). Using .Net programming language and MySQL as the database. Supported by the availability of the Internet network and provider of GPS Tracker, the application is expected to provide easiness like recapitulation receivable, contract data summary, recapitulation of payments that can support the performance of employees of PT. Tatabumi Adhiraya and customer satisfaction as well as reports required by the leadership of the PT. Tatabumi Adhiraya or customers can be seen easily, quickly and accurately.